From the desks of ROS maintainers: A survey of modern & capable mobile robotics algorithms in the robot operating system 2 - Macenski, Steve; Moore, Tom; Lu, David V.; Merzlyakov, Alexey; Ferguson, Michael (Robotics and autonomous systems, 2023)
The Robot Operating System 2 (ROS 2) is rapidly impacting the intelligent machines sector — on space missions, large agriculture equipment, multi-robot fleets, and more. Its success derives from its focused design and improved capabilities targeting product-grade and modern robotic systems. Following ROS 2’s example, the mobile robotics ecosystem has been fully redesigned based on the transformed needs of modern robots and is experiencing active development not seen since its inception. This paper comes from the desks of the key ROS Navigation maintainers to review and analyze the state of the art of robotics navigation in ROS 2. This includes new systems without parallel in ROS 1 or other similar mobile robotics frameworks. We discuss current research products and historically robust methods that provide differing behaviors and support for most every robot type. This survey consists of overviews, comparisons, and expert insights organized by the fundamental problems in the field. Some of these implementations have yet to be described in literature and many have not been benchmarked relative to others. We end by providing a glimpse into the future of the ROS 2 mobile robotics ecosystem. •ROS 2’s Nav2 has a number of new algorithms and capabilities suitable for a large number of applications.•This survey analyzes ROS 2 algorithm’s capabilities and benchmarks performance.•Explains systems provided to build robust autonomous navigation systems in dynamic environments.